2005
DOI: 10.1681/asn.2004040266
|View full text |Cite
|
Sign up to set email alerts
|

Variable Pump Flow–Based Doppler Ultrasound Method

Abstract: Decreasing vascular access flow (Qa) is an important predictor of future access thrombosis and malfunction for hemodialysis (HD) patients. Among all of the methods for determining Qa, the variable pump flow (VPF) Doppler method measures Qa according to the change in Doppler signal between the arterial and the venous needles under different pump flow. After this technique was combined with spectral analysis of Duplex Doppler imaging, the variable pump flow-based Doppler ultrasound method (VPFDUM) for Qa measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…According to Kidney Disease Outcomes Quality Initiative guidelines for vascular access, HD patients with Qa Ͻ600 ml/min or Qa Ͻ1000 ml/min that has decreased by Ͼ25% during 4 mo should be referred for fistulogram to detect potential stenotic lesions (23). Our previous study found that the unassisted patency of vascular access at 6 mo was significantly poorer in patients with Qa Ͻ500 ml/min than in those with Qa Ͼ500 ml/min (13.6 versus 92.2%) (4). Therefore, the increase of Qa may contribute to the higher patency of AVF of our patients in this study.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…According to Kidney Disease Outcomes Quality Initiative guidelines for vascular access, HD patients with Qa Ͻ600 ml/min or Qa Ͻ1000 ml/min that has decreased by Ͼ25% during 4 mo should be referred for fistulogram to detect potential stenotic lesions (23). Our previous study found that the unassisted patency of vascular access at 6 mo was significantly poorer in patients with Qa Ͻ500 ml/min than in those with Qa Ͼ500 ml/min (13.6 versus 92.2%) (4). Therefore, the increase of Qa may contribute to the higher patency of AVF of our patients in this study.…”
Section: Discussionmentioning
confidence: 48%
“…First, we would like to control the interfering effect of the great individual variation in flow. This may explain why there was no statistical significance for Qa 4 even with a difference of 119.4 ml/min between the two groups but there was significance for ⌬(Qa 4 Ϫ Qa 3 ) with only a difference of 48.9 ml/min in Table 3. Second, several incremental changes of Qa were helpful to quantify and elucidate the roles of the various effects (e.g., hemodynamic effect of HD, the thermal and nonthermal effects of FIR) in the change of access flow.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Existen algunos determinantes de la recirculación fistular, lo que incluye la velocidad del flujo de la bomba peristáltica, la posición de las puntas de las agujas, la orientación de las líneas, la estenosis del acceso y el tipo del acceso. Existen múltiples métodos para medir la recirculación, basados en mediciones de urea, glucosa y la termodilución, sin embargo el gold estándar actualmente es el método dilucional con ultrasonido [9,10,[14][15][16][17][18][19][20]. …”
unclassified